Phase composition and properties of Fe₂O₃-Al₂O₃ catalytic system in the high-temperature ammonia oxidation process - Zakharchenko, N.I. (Functional Materials, 2005)
The Fe₂O₃-AI₂O₃ catalytic system in the high-temperature ammonia oxidation reaction has been studied. The system phase composition has been shown to influence the physicochemical properties and performance of the catalysts. The catalytic properties of the iron-aluminum system (93.3 mass % by Fe₂O₃ and 6.7 mass % by Al₂O₃) in ammonia oxidation have been determined. The causes of high-temperature catalyst deactivation have been discussed. Исследована каталитическая система Fe₂O₃-AI₂O₃ в реакции высокотемпературного окисления аммиака. Показано влияние фазового состава системы на физико-химические и каталитические свойства катализаторов. Для катализатора состава Fe₂O₃ — 93,3 %масс., Al₂O₃ — 6,7 %масс определены оптимальные характеристики процесса окисления аммиака. Рассмотрены причины дезактивации катализатора. Досліджено каталітичну систему Fe₂O₃-AI₂O₃ в реакції високотемпературного окислення аміаку. Показано вплив фазового складу системи на фізико-хімічні і каталітичні властивості каталізаторів. Визначені каталітичні властивості залізо-алюмінійового каталізатора ( Fe₂O₃ — 93,3 мас.%, Al₂O₃ — 6,7 мас.%) окислення аміаку. Розглянуто причини високотемпературної дезактивації каталізатора.